The Effectiveness of Film As A Media in Listening Comprehension - Tri Winindyasari Palupi (STKIP PGRI Banjarmasin, 2021)
Film is an audio-visual art form to present a story to an audience. As an entertainment medium, films can be used as complementary media in delivering language learning materials and training language skills. There are four macro language skills that must be mastered in order to be skilled in communication, namely listening, speaking, reading, and writing. One of the skills, namely listening, uses films as one of the learning materials. In the process of listening comprehension, films can be used to attract students' attention to several aspects of spoken language expression. Introducing and using films as a medium in language learning has been used, including as a tool to increase student interest in learning, expand knowledge and diverse cultures, improve language listening skills, make students familiar with English, and have an impact on increasing vocabulary development. In addition, films have a different effect on the learning process in the classroom because films have the power to motivate students to pay attention to the target language. For this reason, this paper tries to explain how film can be an effective medium in building listening comprehension and to elaborate further on the effectiveness of film as an audio-visual medium during the English listening process.